ONLINE SHOPPING HABIT DALAM MINAT BELI ULANG MELALUI MARKETPLACE - Mulyani, Sri; Meria, Lista (CV. Lafadz Jaya, 2024)
Customer repurchase intentions are critical to the profitability and sustainable growth of online businesses. This study aims to analyze the effect of perceived convenience, trust, e-WOM, perceived value, and satisfaction on repurchase intention. This research takes a descriptive causality research type with a quantitative method approach through a purposive sampling technique and obtained 100 respondents who have bought products on the Tokopedia and Shopee marketplaces in more than 3 purchases in 1 month. This research uses the Structural Equation Model Partial Least Square (SEM-PLS) method. The results of this research indicate that repurchase intention is formed because it is influenced by trust and satisfaction. Furthermore, perceived value is influenced by perceived convenience, but perceived convenience, perceived value, and e-WOM have no effect on repurchase intention. Thus, this research can be an evaluation of the Tokopedia and Shopee marketplaces in increasing the influence of online buying habits.